“Uma pessoa pequena com ações pequenas pode mudar o mundo”: escutando modos de vida e percepções sobre direitos de adolescentes em contextos vulneráveis - Missio, Joana (2020)
The adolescence can assume different characteristics according to history, society and culture. Thus, in the contexts of urban peripheries, the exclusion and social vulnerability can be constituted as crossings of the adolescents‟ experiences. From these specificities, it becomes important to reflect about the rights of this population and the best ways of listen to them in their needs, in order to consolidate and guarantee these rights. Thereby, the objective was to listen to adolescence experiences, wais of life and perceptions about the rights of adolescents in a context of social vulnerability. To this end, a qualitative research with eleven adolescents, from twelve to fourteen years old, students of a philanthropic school located on the periphery of a city in the interior of Rio Grande do Sul was realized. In this school, semi-structured interviews were first conducted and, based on the emerging themes, two focus groups were planned. The interviews and the groups had their audios recorded and later transcribed. The analysis was made using the thematic content analysis method, and the data was triangulated. It should be noted that ethical precepts were attended in this research, obtaining approval from the Comitê de Ética em Pesquisa da Universidade Federal de Santa Maria. As main results, there are some singularities that were presented by the participants regarding the meanings of adolescence, such as: the abandonment of playing upon the arrival of responsibility as a demarcator of becoming an adolescent, the urgency to work as a result of the precarious socio-economic situation, the differentiation between the “service” and “dream” as future projects. In addition, regarding the perceptions about rights, although they expressed an initial estrangement, the participants demonstrated a critical and questioning stance, claiming the rights to choice, expression, freedom, work, among others. It can also be perceived the necessity of feeling listened and valued in their opinions. Thus, it is understood the importance of spaces where adolescents can not only talk and share experiences, but also spaces of effective social participation and consideration of their voices. Still, it is necessary discussing about work for adolescents in its interface with education and with public policies that mitigate the urgency of the contribution to family income. Finally, the singularities of these adolescents need to be considered, so that they can be participatory agents and transformers, transposing, in the daily challenges, the vulnerabilities that arise.